Menanamkan Pendidikan Wawasan Nusantara Dalam Membentuk Karakter Siswa-Siswi Smp Negeri 2 Hilimegai - Maestro Laia; Hendrikus Otniel Nasozaro Harefa (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
This research examines the implementation of Archipelago Insight education in shaping student character at SMP Negeri 2 Hilimegai. Through a descriptive qualitative approach with observation and interviews, it was found that teachers play an active role in instilling national values through contextual learning and class discussions. Students showed tolerance and respect for differences. Challenges such as students' lack of interest were overcome with creative teaching methods. Parental support and activities such as singing national anthems and cultural discussions also strengthen the value of nationalism. As a result, character education based on Archipelago Insight has proven effective in forming students with integrity and love for the country.